The influence of corporate governance and financial performance on disclosure of Islamic Social Reporting - Sofa Ayuk Mustika; Wulan Suci Rachmadani; Fany Indriyani (Islamic Accounting Journal, 2021)
This research is motivated by the disclosure of Islamic Social Reporting (ISR) because it needs to be implemented by Islamic banks in meeting the expectations of stakeholders, especially the Muslim community. The purpose of this study is to find out the effect of Good Corporate Governance (GCG) and Financial Performance on Islamic Social Reporting (ISR) Disclosures with Non-Performing Financing (NPF) as Intervening Variables in Islamic Commercial Banks in Indonesia (2016-2020 Period). The research data collection method is by using secondary data sourced from the Annual Reports of each Islamic bank from 2016 to 2020. The results show that the variables of the Board of Commissioners, and Financial Performance are able to influence the Disclosure of Islamic Social Reporting (ISR) while the Sharia Supervisory Board, Audit Committee, Institutional Ownership does not affect Islamic Social Reporting (ISR) Disclosures. The variables of the Audit Committee and Institutional Ownership mediated by Non-Performing Financing (NPF) are able to influence the Disclosure of Islamic Social Reporting (ISR) while the Board of Commissioners, Sharia Supervisory Board, and Financial Performance mediated by Non-Performing Financing (NPF) do not affect the Disclosure of Islamic Social Reporting (ISR).Keywords: Good Corporate Governance, Islamic Social Reporting, Non-Performing Financing